City lab as a platform for implementing urban innovation. The role of companies - Kopyciński, Piotr (International Entrepreneurship Review, 2018)
This article has two aims. The first one is to show city lab as a specific innovation management platform in urban areas, whereas the other is to present the reasons why companies should get involved in it. The article begins by showing how the perception of innovation evolved from a strictly technological notion to an approach associated with satisfying social needs (social and urban innovation). Next, the understanding of city lab will be presented, taking into account the well-known living lab concept. Subsequently, based on the quadruple helix concept, city lab actors will be discussed (public authorities, enterprises, city users, scientific units and intermediaries), as well as their roles, against the background of public-private-people partnerships (4P). Considering these observations, similarities and differences between living lab and city lab will be identified. By way of conclusion, the article offers a handful of reasons why companies, especially multinational ones, should get involved in city lab initiatives.